Efficacy and safety of intravenous iron sucrose in treating adults with iron deficiency anemia - Cançado,Rodolfo Delfini (2011)
BACKGROUND: Iron deficiency is the most common disorder in the world, affecting approximately 25% of the world`s population and the most common cause of anemia. OBJECTIVE: To evaluate the efficacy and safety of intravenous iron sucrose (IS) in the treatment of adults with iron deficiency anemia METHODS: Eighty-six adult patients with iron deficiency anemia, who had intolerance or showed no effect with oral iron therapy, received a weekly dose of 200 mg of intravenous iron sucrose until the hemoglobin level was corrected or until receiving the total dose of intravenous iron calculated for each patient RESULTS: The mean hemoglobin and serum ferritin levels were 8.54 g/dL and 7.63 ng/mL (pre-treatment) and 12.1 g/dL and 99.0 ng/mL (post-treatment) (p-value < 0.0001), respectively. The average increases in hemoglobin levels were 3.29 g/dL for women and 4.58 g/dL for men; 94% of male and 84% of female patients responded (hemoglobin increased by at least 2 g/dL) to intravenous iron therapy. Correction of anemia was obtained in 47 of 69 (68.1%) female patients and in 12 of 17 male (70.6%) patients. A total of 515 intravenous infusions of iron sucrose were administered and iron sucrose was generally well tolerated with no moderate or serious adverse drug reactions recorded by the investigators. CONCLUSIONS: Our data confirm that the use of intravenous iron sucrose is a safe and effective option in the treatment of adult patients with iron deficiency anemia who lack satisfactory response to oral iron therapy. Intravenous iron sucrose is well tolerated and with a clinically manageable safety profile when using appropriate dosing and monitoring. The availability of intravenous iron sucrose would potentially improve compliance and thereby reduce morbidities from iron deficiency.